Factor VIII-Factor IX Interactions: Molecular Sites Involved in Enzyme-Cofactor Complex Assembly - Mertens, Koen; Celie, Patrick H.N.; Kolkman, Joost A.; Lenting, Peter J. (Thrombosis and Haemostasis, 1999)
The activation of factor X is one of the steps in the coagulation cascade that is driven by the assembly of an activated serine protease with a membrane-bound cofactor. In the initial phase of coagulation, factor X is activated by the complex of activated factor VII (factor VIIa) and tissue factor. Subsequently, during the so-called propagation phase, factor X activation is catalyzed by the complex of activated factor IX (factor IXa) and activated factor VIII (factor VIIIa). In these complexes, factor VIIa and factor IXa are the factor X-activating enzymes, whereas tissue factor and factor VIIIa serve as non-enzymatic cofactors.1 Factors VIIa and IXa are highly homologous to other cofactor-dependent enzymes, such as activated factor X (factor Xa) and activated protein C, both in amino acid sequence, domain organization, and three-dimensional structure.2 Factor VIIa and IXa further share low or negligible activity towards their natural substrate factor X, unless in complex with their physiological cofactors.Although tissue factor and factor VIIIa serve similar roles as biological amplifiers, they are structurally different. Tissue factor is a small, transmembrane protein with an extracellular part comprising 219 amino acids. Factor VIII is much larger (2,332 amino acids), circulates in plasma, and requires proteolytic processing to exert its biological activity.3 When cofactors are assembled with their respective enzymes, a dramatic increase in enzymatic activity occurs. The underlying molecular mechanism, however, remains poorly understood.During the past few years, remarkable progress has been made in understanding the molecular details of enzyme-cofactor assembly within the coagulation cascade. Crystallography has provided high-resolution structures of tissue factor4 and the various cofactor-dependent coagulation enzymes.2 Moreover, the crystal structure of the factor VIIa—tissue factor complex has been resolved and has allowed the identification of the molecular sites involved in enzyme-cofactor interaction.5,6 Such details are still lacking, however, for the factor IXa—factor VIIIa complex. Current views are derived from three-dimensional models generated by homology modeling based on structurally-related proteins, such as nitrite reductase,7 ceruloplasmin,8 and galactose oxidase.9 Despite their inherent limitations, these models greatly facilitate the interpretation of previous functional studies on factor X activation. As such, the availability of molecular models may be considered an important step toward resolving the structure of the factor IXa—factor VIIIa complex and understanding the role of complex assembly and defects thereof. This chapter provides an overview of the current developments in this field.